ANALYSING THE DYNAMICS OF HUMAN INNOVATION IN ADMINISTRATION - Prety Diawati; Silvy Sondari Gadzali; Ardhana Januar Mahardhani; Bambang Irawan; Abu Muna Almaududi Ausat (Jurnal Ekonomi, 2023)
Talking about innovation or novelty is certainly done through a process with stages based on standard operating procedures that have been set. What is meant by standard operating procedure here is a concept that describes or explains the work mechanism or work procedures carried out by humans through a process of cooperation between two or more humans so that the results achieved always display or find novelty. This research aims to explain the dynamics of human innovation in administration through language that is easy to understand. This research includes library research because this research is conducted to search, analyse, interpret and generalise from the facts of the results of thoughts and ideas written by innovation experts in administration. This research is descriptive qualitative with a secondary data analysis approach. The results of this research show that there are several novelties that humans must produce in administration, namely novelty in model or form, novelty in quality, and novelty in quantity. The results of this study can be used as a reference for anyone with an interest in discussing administrative topics. In addition, it can be a material for formal discussion in higher education.